Peculiarities of hormonal, macro- and microelemental status in wrestlers - D. S. Korolev; M. V. Ivkina; A. N. Arkhangelskaya; K. G. Gurevich (National Electronic Information Consortium (NEICON), 2021)
Objective: to determine the content of hormones, as well as some macro- and microelements in athletes-wrestlers outside the period of competition and active training.Materials and methods: the study involved 66 athletes-wrestlers and 107 students involved in sports professionally. The level of hormones and vitamin D was determined by the ELISA method. To analyze the content of macro- and microelements, the subjects were cut off a lock of hair from the back of the head in an amount of at least 0.1 g. The studies were carried out on an ICP-MS Agilent 7900 mass spectrometer.Results: levels of cortisol, TSH and T4 are higher, and levels of testosterone, T3 and vitamin D are lower in athletes compared to the control group. An increase in the content of sodium, calcium, potassium, magnesium, cobalt and a decrease in iodine were revealed in fighters from those who were not involved in sports professionally.Conclusion: the data obtained indicate an imbalance in the work of the body's endocrine systems and impaired adaptation to stress. It is known that the determination of the hormonal status is used to assess the adaptation, the revealed changes in the indicators of vitamin D, macro- and microelements, allow the study of these indicators in order to prevent the syndrome of overtraining of athletes, to maintain and improve sports performance.